Combined Chylothorax and Chylous Ascites Complicating Liver Transplantation: A Report of a Case and Review of the Literature - Tommy Ivanics; Semeret Munie; Hassan Nasser; Shravan Leonard-Murali; Atsushi Yoshida; Shunji Nagai; Kelly Collins; Marwan Abouljoud; Michael Rizzari (Case Reports in Transplantation)
Chyle leaks may occur as a result of surgical intervention. Chyloperitoneum, or chylous ascites after liver transplantation, is rare and the development of chylothorax after abdominal surgery is even more rare. With increasingly aggressive surgical resections, particularly in the retroperitoneum, the incidence of chyle leaks is expected to increase in the future. Here we present a unique case of a combined chylothorax and chyloperitoneum following liver transplantation successfully managed conservatively. Risk factors for chylous ascites include para-aortic manipulation, extensive retroperitoneal dissection, use of a Ligasure device, and early enteral feeding as well as early enteral feeding. The clinical presentation is typically insidious and may include painless abdominal distension. Diagnosis can be made by noting characteristic milky white drainage which on laboratory examination has a total fluid triglyceride level >110 mg/dl, an ascites/serum triglyceride ratio of >1 and a leukocyte count in fluid >1000/uL with a lymphocyte predominance. Chyle leaks may lead to significant morbidity and mortality. Numerous management options exist, with conservative nonoperative measurements leading to the most consistent and successful outcomes. This includes a step-up approach beginning with dietary modifications to a low-fat or medium chain triglyceride diet followed by nil per os with addition of total parenteral nutrition and somatostatin analogues such as octreotide. Rarely do patients require more invasive treatment. Early recognition and appropriate management are imperative to mitigate this complication.